2006
DOI: 10.1111/j.1365-4632.2006.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive macular hypomelanosis in Singapore: a clinico‐pathological study

Abstract: PMH may occur among young adults in Singapore. Its etiology is uncertain. The melanin content of lesional skin appears to be less than that in normal sites. EM shows a higher ratio of immature melanosomes in lesional vs. normal skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 4 publications
2
43
3
1
Order By: Relevance
“…[1][2][3] In some patients, transient repigmentation is seen following exposure to sunlight. 4 The etiology of PMH is unknown and has been the subject of much research.…”
Section: Comunicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In some patients, transient repigmentation is seen following exposure to sunlight. 4 The etiology of PMH is unknown and has been the subject of much research.…”
Section: Comunicationmentioning
confidence: 99%
“…2 Resident Physician in Dermatology, University of Pernambuco (UPE), Recife, Pernambuco, Brazil. 3 PhD. Full Professor, Department of Infectious and Parasitic Diseases, Federal University of Pernambuco (UFPE), Recife, Pernambuco, Brazil.…”
mentioning
confidence: 99%
“…The absence of patients over 40 years of age suggests that PMH may be a self-limiting disease, as has already been reported in other studies. 1,3,6 The time of progression of the disease was also found to be variable, ranging from 1 to 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions are asymptomatic and there have been no precedents of inflammatory lesions. [1][2][3][4][5] Its pathogenesis remains unclear. Some authors have suggested the effect of a subspecies of Propionibacterium acnes in the physiopathology of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…. ‹mmünohistokimya: Yap›lan çal›flmalarda hipopigmente maküller ile komflu sa¤lam deri, melanosit morfolojileri ve say›la-r› bak›m›ndan immunhistokimyasal olarak S-100 boyama ile karfl›laflt›r›ld›¤›nda anlaml› fark bulunmam›flt›r 6,11 . Wu ve arkadafllar› S-100 boyas› melanositlere spesifik olmad›¤›ndan immunhistokimyasal olarak S-100 yan›nda tirozinaz related protein 1 (TRP-1) ve tirozinaz (T311) boyalar› da kullanm›fllar ancak her üç boyamada da normal deri ile karfl›laflt›r›ld›¤›nda hipopigmente maküllerde melanosit say›s› ve morfolojisi aç›s›n-dan istatistiksel olarak anlaml› fark saptamam›fllard›r 3 .…”
Section: Epidemiyolojik Ve Klinik öZelliklerunclassified